Political Strategy of the Democratic Party in Increasing Women's Representation in the Legislative Body of Ciamis Regency for the 2024–2029 Period - Arie Budiawan Asep Nurdin Rosihan Anwar, Yoga Gustiadi; Arie Budiawan; Asep Nurdin Rosihan Anwar (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study aims to explore and analyze the political strategy of the Democratic Party in increasing women’s representation in the legislative body of Ciamis Regency for the 2024–2029 period. The background of this research stems from the low level of female representation in the Regional House of Representatives (DPRD) of Ciamis Regency, which only reached 10% or 5 out of 50 members, despite national regulations mandating a 30% gender quota. This study adopts a qualitative approach with descriptive methods, using interviews, observations, and documentation as data collection techniques. The theoretical framework is based on Schroder’s political strategy theory, which divides strategies into offensive and defensive categories. The findings indicate that the Democratic Party's offensive strategies involve electoral mapping, strengthening women's networks, and nominating influential female candidates. Meanwhile, its defensive strategies include voter segmentation, the formulation of gender-based campaign programs, and the protection of core voter bases. However, challenges persist in the form of limited female political resources, lack of internal party training, and weak financial support. Therefore, the Democratic Party needs to strengthen its cadre development, provide logistical support, and carry out sustained affirmative campaigns to achieve gender equality in local politics. This study contributes to the development of more inclusive and gender-responsive party policies. Keywords: Political strategy, Democratic Party, women’s representation, legislative, Ciamis.